IDENTIFICATION AND PHYLOGENETIC ANALYSIS OF NINE CYST NEMATODE POPULATIONS FROM MAIN FIELD CROPS IN CHINA - Y. X. Feng; D. Wang; Y. H. Xuan; L.J. Chen; Y. Y; Wang; X. Y. Liu; Y. Chen; X. P. Lu; X. F. Zhu; Y. X. Duan (Journal of Animal and Plant Sciences, 2018)
Cyst-forming nematodes, a major category of plant parasitic nematodes, cause severe yield losses in many crop plants and are a serious threat to food production in China. However, the reports focused on identification of species abundance and distribution of cyst nematodes on main crops in China are fewer. During 2012-2014, nine populations of cyst nematodes collected from various locations in major crop cultivation areas of China were identified as four species (Heterodera glycines, H. avenae, H. filipjevi, H. elachista) based on morphology and molecular analysis. H. filipjevi and H. elachista were first discovered in Anhui and Jiangxi Provinces, respectively. In addition, a PCR-ITS-RFLP method was applied to distinguish all the studied populations, which revealed molecular characteristics of cyst nematode species on major field crops in China. The present study broadens the knowledge regarding distributions and molecular features of vital Heterodera species and populations, and will also provide useful information for early protection of cystnematodes in China. and Guangxi Provinces. It is necessaryto investigate and
Keywords: cyst nematode; distribution; identification; rDNA-ITS; RFLP; China.